Circles within circles: crosstalk between protein Ser/Thr/Tyr-phosphorylation and Met oxidation - Rao, R Shyama Prasad (BioMed Central, 2013)
BACKGROUND: Reversible posttranslational protein modifications such as phosphorylation of Ser/Thr/Tyr and Met oxidation are critical for both metabolic regulation and cellular signalling. Although these modifications are typically studied individually, herein we describe the potential for cross-talk and hierarchical regulation. RESULTS: The proximity of Met to Ser/Thr/Tyr within the proteome has not previously been addressed. In order to consider the possibility of a generalized interaction, we performed a trans-kingdom sequence analysis of known phosphorylation sites in proteins from bacteria, fungi, plants, and animals. The proportion of phosphorylation sites that include a Met within a 13-residue window centered upon Ser/Thr/Tyr is significantly less than the occurrence of Met in proximity to all Ser/Thr/Tyr residues. Met residues are present at all positions (-6 to +6, inclusive) within the 13-residue window that we have considered. Detailed analysis of sequences from eight disparate plant taxa revealed that many conserved phosphorylation sites have a Met residue in the proximity. Results from GO enrichment analysis indicated that the potential for phosphorylation and Met oxidation crosstalk is most prevalent in kinases and proteins involved in signalling. CONCLUSION: The large proportion of known phosphorylation sites with Met in the proximity fulfils the necessary condition for cross-talk. Kinases/signalling proteins are enriched for Met around phosphorylation sites. These proteins/sites are likely candidates for cross-talk between oxidative signalling and reversible phosphorylation.